O manejo da abertura da barra influencia a comunidade de macroinvertebrados nas áreas úmidas do sul do Brasil? Um estudo de caso no Parque Nacional da Lagoa do Peixe - Crippa, Liziane Bertotti (Universidade do Vale do Rio dos Sinos, 2011)
The Lagoa do Peixe located in the Parque Nacional da Lagoa do Peixe – South of Brazil - has its connection with the sea artificially opened every year in the end of winter. However, this management is being accomplished without assessing the impacts of the sandbar opening in the aquatic biodiversity of the region’s humid areas. The following questions were tested in this study: 1) The richness, the abundance and the composition of macroinvertebrates in the wetlands of the Lagoa do Peixe vary temporally with the opening and closing of the sandbar? 2) The macroinvertebrates community range’s pattern varies with the opening and closing of the sandbar? A total of four collections was accomplished between March and October 2008 in three humid areas located in the Lagoa do Peixe flooding plain that were influenced by the artificial opening of the sandbar in two humid areas without being influenced by the opening of the sandbar (control areas). A total of 19,333 individuals distributed in 45 families of aquatic macroinvertebrates was sampled in the humid areas studied. The macroinvertebrates richness (F1,3= 41, 645, p = 0, 008) and abundance (F1,3= 1499,37; p < 0, 001) were superior in the humid areas that weren’t influenced by the artificial opening of the sandbar (control areas) than in those ones subjected to the opening of the sandbar. The macroinvertebrates composition significantly ranged between the humid areas subjected and the ones not subjected to opening of the sandbar (F1,16= 6, 2422, p < 0, 001). The obtained results in this study indicate that the artificial opening of the Lagoa do Peixe sandbar affects the dynamics of the associations of aquatic macroinvertebrates in humid coastal areas in the South of Brazil.
Keywords: Abertura barra; Lagoa costeira; Parque nacional; Macroinvertebrados; Sandbar; Coastal lagoon; National park; Macroinvertebrates; ACCNPQ::Ciências Biológicas::Biologia Geral